From Wild West to the godfather enforcement market structure - Anderson, James E. 1943- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 2001)
Weak states enable private enforcement but it does not always fade away in the presence of strong states. We develop a general equilibrium model of the market organization of enforcers (self-enforcers, competitive specialized enforcers or monopoly) who defend endowments from predators. We provide conditions under which a Mafia emerges, persists and is stable. Mafias are most likely to emerge at intermediate stages of economic development. Private enforcers might provide better enforcement to the rich than would a welfare-maximizing state - hence the State may find it difficult to replace the Mafia or competitive private enforcers.